2021
DOI: 10.1007/s10238-021-00691-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis-5 predicts end-stage renal disease in patients with microscopic polyangiitis and granulomatosis with polyangiitis without substantial liver diseases

Abstract: We previously reported that fibrosis-4 (FIB-4) was associated with poor outcomes of microscopic polyangiitis (MPA) and granuloma with polyangiitis (GPA). We also investigated the potential of FIB-5, a novel index, in predicting all-cause mortality and end-stage renal disease (ESRD) during follow-up in patients with MPA and GPA without substantial liver diseases. Clinical and laboratory data at diagnosis were collected by reviewing the medical records of 180 patients with MPA and GPA. FIB-5 was obtained by a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A recent study has shown that FIB-5 performed better than FIB-4 in differentiating between non-significant and significant hepatic fibrosis among patients with chronic hepatitis C. 40 Moreover, a retrospective study has shown a negative relationship between the level of FIB-5 and the occurrence of ESRD during the follow-up in patients with microscopic polyangiitis and granuloma with polyangiitis without substantial liver diseases. 41 The present study also found that FIB-5 had the highest predictive ability for CA-AKI compared with other LFSs in patients undergoing elective PCI. However, no studies have investigated the association between FIB-5 and CA-AKI.…”
Section: Discussionsupporting
confidence: 76%
“…A recent study has shown that FIB-5 performed better than FIB-4 in differentiating between non-significant and significant hepatic fibrosis among patients with chronic hepatitis C. 40 Moreover, a retrospective study has shown a negative relationship between the level of FIB-5 and the occurrence of ESRD during the follow-up in patients with microscopic polyangiitis and granuloma with polyangiitis without substantial liver diseases. 41 The present study also found that FIB-5 had the highest predictive ability for CA-AKI compared with other LFSs in patients undergoing elective PCI. However, no studies have investigated the association between FIB-5 and CA-AKI.…”
Section: Discussionsupporting
confidence: 76%
“…For variables other than ALT which is closely related to liver damage, the systemic inflammation due to AAV could subsequently increase their serum level and should be considered when analysing the result. As for AST, FIB-5, for which AST is a parameter located in the numerator of the equation, was proven to significantly predict ESRD in patients with MPA and GPA without substantial liver diseases ( 31 ). In addition, AST levels may be elevated in cardiovascular diseases including myocarditis and ischaemic heart disease in AAV patients ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study retrospectively screened 287 AAV patients by reviewing their medical records and included 260 patients in this study based on the inclusion criteria as follows: i) all patients met both the 2012 revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides and the 2007 European Medicine Agency algorithm for the classification of AAV [ 1 , 2 ]; ii) the first classification of AAV was made at this hospital from October 2000 to December 2021; iii) the electronic medical records were well-written sufficiently for collecting clinical, laboratory, radiological, and histological data [ 3 , 4 ]; iv) the parameters composing the equation for HSI were particularly included in clinical and laboratory data [ 13 , 14 ]; v) patients with the concurrent serious medical conditions mimicking AAV, such as malignancies and infectious diseases at AAV diagnosis, were excluded [ 9 - 12 ]; vi) the follow-up duration was more than three months after the AAV diagnosis; vii) AAV patients who have been exposed to glucocorticoids >20 mg (equivalent to prednisolone) or immunosuppressive drugs before the AAV diagnosis were excluded [ 9 - 12 ]; and viii) patients who took drugs that could provoke false positivity of ANCA, such as propylthiouracil and hydralazine, were also excluded [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, apart from the liver involvement of AAV, several studies on the link between liver fibrosis-related indices and poor outcomes of AAV have been conducted [8][9][10][11][12]. These studies found that although AAV did not directly cause serious liver fibrosis, liver fibrosis-related indices at AAV diagnosis could forecast poor outcomes of AAV during the disease course.…”
Section: Nomenclature Of Vasculitides and The 2007 European Medicinementioning
confidence: 99%